Prostate Cancer Stereotactic Body Radiation Therapy with Image-guided Radiation Therapy (IGRT) Technique with Three-Dimensional Transperineal Ultrasound for IGRT Tracking of the Prostate - Igor Migowski; Arn Migowski (Brazilian Journal of Oncology)
Introduction Ultrahypofractionated radical radiotherapy for prostate cancer, also known as stereotactic body radiation therapy (SBRT), is an unprecedented modality of prostate radiotherapy and is still used very sparsely in Brazil. The use of fiducial implants and spacers may make it even more difficult to implement prostate SBRT on a large scale in Brazil. We describe a completely non-invasive technique for the treatment of localized prostate cancer with stereotactic body radiotherapy.